An interactive computer-based training system for electrical engineering education (synchronous generator) / Khairulnizam Khamis - Khamis, Khairulnizam (2000)
This report describes an interactive computer-based training system (ICBTS) developed for synchronous machine. The software is developed using visual basic (VB) programming to improve the conventional teaching style by providing interactive notes, animated graphics, working examples and quiz in order to make more attractive and understanding in learning process. This software allows own assessment by the users, enabling them to step in at their current levels.